Holt-Oram syndrome: a clinical genetic study. Issue 4 (April 1996) - Newbury-Ecob, R A; Leanage, R; Raeburn, J A; Young, I D
Abstract : A clinical and genetic study of the Holt-Oram syndrome (HOS) has been carried out in the United Kingdom involving 55 cases designated Holt-Oram syndrome, together with their parents and sibs. Data from the clinical assessment of both familial and isolated cases were used to define the HOS phenotype and to outline the spectrum of abnormalities, especially factors affecting severity. Skeletal defects affected the upper limbs exclusively and were bilateral and asymmetrical. They ranged from minor signs such as clinodactyly, limited supination, and sloping shoulders to severe reduction deformities of the upper arm (4.5%). The radial ray was predominantly affected than the right. All affected cases showed evidence of upper limb involvement. Cardiac defects were seen in 95% of familial cases and included both atrial septal defect (ASD, 34%) and ventricular septal defect (VSD, 25%); 39% had only ECG changes. Cardiac involvement ranged from asymptomatic conduction disturbances to multiple structural defects requiring surgery in infancy. Sudden death could be caused by heart block. Inheritance was autosomal dominant with 100% penetrance and no evidence of reduced fitness. Increasing severity occurred in succeeding generations consistent with anticipation.